2015
DOI: 10.1105/tpc.114.135400
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis RIC1 Severs Actin Filaments at the Apex to Regulate Pollen Tube Growth

Abstract: Pollen tubes deliver sperms to the ovule for fertilization via tip growth. The rapid turnover of F-actin in pollen tube tips plays an important role in this process. In this study, we demonstrate that Arabidopsis  thaliana RIC1, a member of the ROP-interactive CRIB motif-containing protein family, regulates pollen tube growth via its F-actin severing activity. Knockout of RIC1 enhanced pollen tube elongation, while overexpression of RIC1 dramatically reduced tube growth. Pharmacological analysis indicated that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
57
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(57 citation statements)
references
References 50 publications
(82 reference statements)
0
57
0
Order By: Relevance
“…Conversely, AtRIC4 in response to Ca 2+ promotes F-actin assembly (Gu et al, 2005). Additionally, recent studies investigating the apical PMlocalized AtRIC1 add to the importance of RIC to regulate actin (Zhou et al, 2015b). Similar to AtRIC3, AtRIC1 binds to and severs F-actin in the presence of Ca 2+ .…”
Section: Cytoskeleton and Ion Dynamicsmentioning
confidence: 99%
“…Conversely, AtRIC4 in response to Ca 2+ promotes F-actin assembly (Gu et al, 2005). Additionally, recent studies investigating the apical PMlocalized AtRIC1 add to the importance of RIC to regulate actin (Zhou et al, 2015b). Similar to AtRIC3, AtRIC1 binds to and severs F-actin in the presence of Ca 2+ .…”
Section: Cytoskeleton and Ion Dynamicsmentioning
confidence: 99%
“…Besides binding to actin filaments, our previous study showed that RMD also is a microtubule-stabilizing protein . Several previous investigations showed that treatment with the microtubuledepolymerizing chemical oryzalin causes no obvious effect on pollen tube growth (Bou Daher and Geitmann, 2011;Zhou et al, 2015), suggesting a minimal function of microtubules on pollen tube growth (Cai et al, 1997). In addition, unlike the role of formins in nucleating the unbranched actin filaments, the actin-related protein2/3 (ARP2/3) complex is known to form a branched actin network (Cheung and Wu, 2004).…”
Section: Tip Localization Of Rmd Is Essential For F-actin Organizatiomentioning
confidence: 99%
“…At the subapex, actin filaments form regular structures in different species, such as the collar, fringe, mesh, or funnel, and some observations indicated that subapical F-actin could regulate the accumulation of vesicles and the growth of the tip region (Gibbon et al, 1999;Fu et al, 2001;Vidali et al, 2001;Chen et al, 2002;LovyWheeler et al, 2005;Qu et al, 2017). At the apex, actin filaments are generally less abundant but are highly dynamic with dense actin structures, which mediates the interaction between the apical/subapical PM and the cytoplasm during rapid tube elongation (Fu et al, 2001; Lee and Yang, 2008;Cai and Cresti, 2009;Cheung et al, 2010;Qu et al, 2013;Rounds et al, 2014;Zhou et al, 2015;Qu et al, 2017). Recently, Qu et al, (2017) demonstrated that F-actin originating from the apical membrane forms a specialized structure consisting of longitudinally aligned actin bundles at the cortex and inner cytoplasmic filaments with a distinct distribution, which plays a pivotal role in the regulation of the growth of the pollen tube tip in Arabidopsis (Arabidopsis thaliana).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The severing activity of plasma membrane-localized RIC1 mediates the release of F-actin from the pollen tube apical plasma membrane into the cytoplasm. RIC1 also contributes to severing F-actin and capping the barbed ends in the cytoplasm (Zhou et al, 2015).…”
Section: Regulation Of Pollen Tube Tip Growthmentioning
confidence: 99%